ИСПАНИЯДАН КЕЛТИРИЛГАН “МУРCИАНА-ГРАНАДИНА” ЭЧКИ ЗОТИНИНГ ҚОРАҚАЛПОҒИСТОН ШАРОИТИДА БИО-МАҲСУЛДОРЛИК ХУСУСИЯТЛАРИ - А. У.Торешова (International Engineering Journal For Research & Development, 2021)
In this article, there are some biological and productive features imported from Spain the goat breeds "Murcina-Granadina" as well as conclusions on adaptation, prospects and their development in the Republic of Karaklpakstan.